MANAGEMENT AND OUTCOME OF RADIOTHERAPY FOR BREAST CANCER : A COMPREHENSIVE SYSTEMATIC REVIEW - Angeline, Wiedya Kristianti; Hartanto, Felix (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: A key component of breast cancer treatment is breast irradiation therapy, which provides the best control and precision. Fractionated whole-breast irradiation, or WBI, is the recommended approach for best outcomes. The goal of this study is to conduct a thorough evaluation of the literature from the previous ten years about the administration and results of radiation therapy for breast cancer. Methods: Using the PRISMA 2020 principles, this systematic review concentrated on full-text English literature that was published between 2014 and 2024. Submissions without a DOI, editorials, and review papers from the same publication were not taken into consideration. Online resources like ScienceDirect, SagePub, and PubMed were used to compile the literature. Result: More than 100,000 papers were first obtained by our research team from reliable sources like Science Direct, PubMed, and SagePub. Only six publications were found to be directly relevant to our ongoing systematic review using a rigorous three-level screening approach. These articles were then chosen for additional examination by in-depth full-text reading. Conclusion: An essential component of breast cancer treatment is adjuvant radiation, which eliminates any remaining cancer in the surgery room and surrounding satellites. Shorter courses are preferred for patients with localized breast cancer to preserve early-stage illness and manage tumors.